Efeito da adubação com fósforo e potássio na toxidez de ferro em arroz irrigado - Farias, Marla de Oliveira (2007)
The iron toxicity may cause considerable reduction in rice productivity, depending on the intensity of symptoms and on the affected farming area. It is necessary to identify the factors that determine the occurrence of this nutritional disorder, as well as, the possible involvement of other nutrients, such as phosphorus and potassium, in its intensity. The objectives of this work were: (1) to determine the effect of phosphorus and potassium adubation on the iron toxicity; (2) to evaluate the development of the symptoms in the aerial part of the plants (BR-IRGA 409 cultivar) and (3) to test whether the symptoms occur when the relative concentration of Fe2+, in relation to the sum of the concentrations of divalent cations (Fe2+, Mn2+, Ca2+, and Mg2+) in the solution is very high. Hence, in green house, a factorial experiment 5x2 (five soils and two adubation levels with phosphorus and potassium), completely randomized design, with two repetitions, was conducted. The adubation levels were zero and 100 mg dm-3 of P and K. The evaluated indicators were visual symptoms of the aerial part of the plants, production of dry matter, content of macro and micronutrients in the tissue of Ca2+, Mg2+, Fe2+ and Mn2+ in the soil solution. The statistical analysis were carried using Analysis of Variance (Duncan test) at 5% probability. The phosphorus and potassium adubation promoted accented increase in the production of dry matter of the plants in all soils, however there was no effect of this adubation neither in the contents of the divalent cations in the tissue, nor in the concentrations of those in the solution. The model of the relation between the molar fraction in the tissue and the molar fraction in the soil solution depended on the cation: Ca, Mg and Mn which showed tendency for saturation. The absorption of Fe remained constant up to a molar fraction of 0,4 (above that it increased exponentially). In molar fraction of Fe up to 0,6 (maximum value obtained in the experiment) the plants did not show symptoms of iron toxicity.